Corrosion-resistant modified water-based aluminum paste as well as preparation method and application thereof
By using alkaline silicon sol and fatty acids to form multi-layer structural coating in aqueous aluminum silver paste, the problem of insufficient corrosion resistance of aqueous aluminum silver paste is solved, and high corrosion resistance, whiteness and brightness are achieved, and suitable for water-based coatings. Widely used.
Patent Information
- Application Number
- CN202411254789.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing water-based aluminum silver paste has insufficient corrosion resistance, the SiO2 coating process is high and is not conducive to large-scale production, the SiO2 layer has low density, and the organic film coating reaction conditions are complex and not strong, making it difficult to achieve high-efficiency and low-cost second-class Metahybrid layer coating.
The alkaline silicon sol capsule film and fatty acid organic film are used to coat aluminum powder in sequence to form a multi-layer structure floating aluminum powder. The dense SiO2 layer is formed by hydrolysis of silane coupling agent and alkaline silicon sol, and fatty acids and alkaline silicon are used to form a Sol bonding forms a stable hydrophobic film, improving the corrosion resistance of aluminum and silver paste.
It realizes high corrosion resistance, whiteness and brightness of aluminum silver paste, and is suitable for various water-based coating systems, avoiding the problems of low density of SiO2 layer and unsolid connection of organic films in traditional processes, and improving the hiding and stability of water surface sex.
Smart Images

Figure CN119119780A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material modification, and in particular relates to a corrosion-resistant modified water-based aluminum-silver paste and a preparation method and application thereof. Background Art
[0002] Aluminum paste has excellent properties such as low price, unique metallic luster, "angle-dependent color" effect and high hiding power, and it has protective and decorative functions, so it is widely used in automotive coatings, industrial coatings, plastic materials and printing inks. As people pay more attention to environmental protection and health, water-based aluminum paste has replaced traditional solvent-based aluminum paste and has become an industry development trend. Compared with traditional solvent-based aluminum paste, water-based aluminum paste has many advantages such as environmental protection, low volatile organic compound content, safe construction and easy use. However, the chemical properties of aluminum are active, and untreated aluminum powder can easily react with acid and alkali to release hydrogen, which poses a great safety hazard. Therefore, it is necessary to treat the surface of aluminum powder to improve the corrosion resistance of aluminum paste.
[0003] In order to improve the corrosion resistance of aluminum-silver paste, the surface of aluminum powder needs to be passivated or coated. At present, SiO2 coating and organic film coating are mainly used to improve the corrosion resistance of aluminum-silver paste. Among them, SiO2-organic binary hybrid film has the characteristics of low toxicity, good corrosion resistance, and little effect on the metallic luster of aluminum powder, and is widely used. The current SiO2 coating process usually uses the hydrolysis of tetraethoxysilane (TEOS) to deposit the SiO2 layer on the surface of aluminum sheet through sol-gel reaction, but the system strictly controls the amount of water, which is costly and not conducive to large-scale production; at the same time, the hydrolysis process of tetraethoxysilane is uncontrollable, resulting in uneven distribution of SiO2 particle size on the surface of aluminum sheet, low density of SiO2 layer, and poor corrosion resistance and whiteness. Organic film coating usually uses small molecular monomers to polymerize in situ on the surface of aluminum sheet, which has the disadvantages of complex reaction conditions and weak direct connection between organic film and inorganic film. Therefore, it is necessary to provide a highly efficient and low-cost binary hybrid layer-coated modified water-based aluminum-silver paste. Summary of the invention
[0004] In view of some deficiencies in the prior art, the present invention provides a corrosion-resistant modified water-based aluminum-silver paste, a preparation method thereof and an application thereof; the present invention sequentially coats the original aluminum-silver paste with an alkaline silica sol capsule film and a fatty acid organic film after modification; the alkaline silica sol capsule film has a high degree of density and is firmly connected to the surface of the aluminum sheet; the carboxyl group of the fatty acid and the hydroxyl group of the alkaline silica sol capsule film are bonded to each other to form a fatty acid organic film with a dense surface; the carboxyl group of the fatty acid in the modified water-based aluminum-silver paste interacts with the surface so that a hydrophobic layer composed of a long carbon chain is generated on the surface of the silver paste, so that the aluminum-silver paste is transformed into a floating aluminum-silver paste, and the dense capsule film composed of the alkaline silica sol improves the corrosion resistance of the aluminum-silver paste; the modified water-based aluminum-silver paste has high corrosion resistance in an alkaline environment, and has floatability, high whiteness and brightness when used in water-based coatings, and can be widely used in various water-based coating systems.
[0005] In order to achieve the above technical objectives, the present invention adopts the following technical effects:
[0006] The present invention first provides a method for preparing a corrosion-resistant modified water-based aluminum-silver paste, the preparation method comprising:
[0007] The original oily aluminum paste raw material is dispersed in an alcohol or ether solvent to form a dispersion, and a silane coupling agent is hydrolyzed on the surface of the aluminum powder to eliminate the organic modifiers on the surface of the oily aluminum paste, and the surface is modified to obtain an aluminum sheet; using alkaline silica sol as a raw material, SiO2-coated flaky aluminum powder is prepared at a certain alkalinity, and then fatty acid hydrophobic organic monomers are coated on the surface of the SiO2-coated flaky aluminum powder to obtain a multilayer structure-coated floating flaky aluminum powder, i.e., the corrosion-resistant modified water-based aluminum paste.
[0008] Preferably, the alcohol or ether solvent includes one or more of ethanol, isopropanol, ethylene glycol or ethylene glycol butyl ether;
[0009] The silane coupling agent includes any one of KH550 (γ-aminopropyltriethoxysilane), KH570 (γ-methacryloxytrimethoxysilane), methyltrimethoxysilane or vinyltrimethoxysilane;
[0010] The fatty acid hydrophobic organic monomer includes one or more of stearic acid, palmitic acid, oleic acid or linoleic acid.
[0011] Preferably, the preparation step comprises:
[0012] (1) dispersing the original aluminum paste raw material in an alcohol or ether solvent, adding a silane coupling agent and water thereto, and then stirring and reacting at a certain temperature, and filtering after the reaction is completed to obtain a modified aluminum paste;
[0013] (2) dispersing the modified aluminum silver paste in an alcohol or ether solvent, then slowly dropping an alkaline silicon solution and an alkaline solution therein, mixing and stirring to react, filtering and washing after the reaction to obtain SiO2-coated flaky aluminum powder;
[0014] (3) dispersing the SiO2-coated flaky aluminum powder in an alcohol or ether solvent, then dropping an isopropanol solution of a fatty acid hydrophobic organic monomer thereinto, vigorously stirring the mixture for reaction, filtering and washing the mixture after the reaction is completed, and obtaining the corrosion-resistant modified water-based aluminum silver paste.
[0015] Preferably, in step (1), the mass ratio of the original aluminum-silver paste raw material, the silane coupling agent and water is 50g:2.5-5g:5g; and the stirring reaction conditions are: reacting at 45-60°C for 1-3h.
[0016] Preferably, in step (2), the mass ratio of the modified aluminum-silver paste, the alkaline silicon solution, and the alkaline solution is 50 g: 5-15 g: 1-3 g;
[0017] The mass concentration of the alkaline silicon solution is 15-30%;
[0018] Preferably, the alkaline solution comprises any one of aqueous ammonia, ethylenediamine or triethylamine.
[0019] Preferably, in step (2), the mixing and stirring reaction conditions are: stirring and mixing the reaction at 45-60° C. for 4-6 hours.
[0020] Preferably, in step (3), the mass ratio of the SiO2-coated flaky aluminum powder to the fatty acid hydrophobic organic monomer is 50 g: 2-5 g;
[0021] The conditions for the vigorous stirring reaction are: vigorous stirring reaction at 40-70° C. for 1-3 hours.
[0022] The present invention also provides a highly corrosion-resistant modified water-based aluminum-silver paste prepared by the above method, wherein the surface of the modified water-based aluminum-silver paste is sequentially coated with an alkaline silica sol capsule film and a fatty acid organic film; the alkaline silica sol capsule film has a high degree of density and is firmly connected to the surface of the aluminum sheet; the carboxyl group of the fatty acid and the hydroxyl group of the alkaline silica sol capsule film are bonded to each other to form a fatty acid organic film with a dense surface.
[0023] The present invention also provides the above-mentioned corrosion-resistant modified water-based aluminum silver paste, which has a wide application in automobile coatings, industrial coatings, plastic materials or printing inks.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention uses alkaline silica sol solution as a silicon source, which can simply and efficiently coat a dense SiO2 layer on the surface of the aluminum sheet, avoiding the problems of uneven SiO2 particle size distribution on the surface of the aluminum sheet, low density of the SiO2 layer, poor corrosion resistance and whiteness caused by the uncontrollable hydrolysis process of traditional tetraethoxysilane. The modified water-based aluminum-silver paste prepared by the method of the present invention has higher corrosion resistance. The present invention uses alkaline silica sol containing polyhydroxyl groups to form a dense capsule film for the first time to coat the water-based aluminum-silver paste, which can effectively block the surface corrosion caused by the contact between the aluminum-silver paste and water, thereby improving the corrosion resistance of the aluminum-silver paste.
[0026] The present invention adopts a method of directly coating a hydrophobic organic layer in a dispersion system, avoiding the problems of a complex reaction mechanism, low density of an organic layer, and loose connection with the surface of an aluminum sheet in the existing coating layer formed by in-situ polymerization; the coating method has the advantages of simple operation, good coating effect, and high product whiteness and brightness. The fatty acid used in the present invention contains two functional groups, polar and non-polar. Through molecular design, the carboxyl polar functional group is chemically bonded to the surface hydroxyl group of the alkaline silica sol to form a stable surface hydrophobic film structure. Compared with the coating method in the prior art in which the functional group is randomly partially bonded to the surface of the aluminum sheet, the coating structure of the present invention is more stable and has a better coating effect.
[0027] The present invention modifies the original aluminum paste and then sequentially coats it with a silica sol capsule film and a stearic acid organic film, so that it has high corrosion resistance, high whiteness, high brightness and high floating properties in an alkaline environment. The floating multi-layer structure coated flaky aluminum powder provided by the present invention has high corrosion resistance in an environment of pH = 11.4 because of the dense silica sol capsule film formed on the surface of the aluminum sheet. Compared with the prior art, the floating aluminum paste provided by the present invention has high corrosion resistance as well as high whiteness and high brightness. In addition, the present invention uses molecular design to allow the carboxyl group of stearic acid to bond with the surface hydroxyl group of the alkaline silica sol to form a stable surface hydrophobic film structure, so that the aluminum paste is transformed into a floating aluminum paste with a water surface covering power of 52200 to 127200 cm 2 / g, can be widely used in various water-based coating systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Fourier infrared spectra of original aluminum-silver paste, Al@SiO2 and Al@SiO2@FA.
[0029] Figure 2 SEM images of original aluminum-silver paste (a), Al@SiO2 (b) and Al@SiO2@FA (c). DETAILED DESCRIPTION
[0030] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0031] Example 1: Preparation of corrosion-resistant modified water-based aluminum paste
[0032] (1) 50 g of the original aluminum silver paste was fully dispersed in 150 g of ethanol, and after stirring and dispersing for more than 1 h, 5 g of methyltrimethoxysilane and 5 g of water were added thereto, and the mixture was stirred and reacted at a water bath temperature of 60° C. for 1 h; after the reaction was completed, the modified aluminum silver paste was obtained by suction filtration and washing;
[0033] (2) Weigh 1 g of triethylamine and dissolve it in 10 g of isopropanol to obtain a triethylamine solution for later use;
[0034] The modified aluminum-silver paste obtained in step (1) was added to 150 g of ethanol and mixed evenly, and then 5 g of alkaline silica sol with a mass concentration of 15% and the above-mentioned triethylamine solution were slowly added thereto for 3 h. After the addition was completed, the mixture was stirred and reacted at a water bath temperature of 45° C. for 4 h. After the reaction was completed, the aluminum-silver paste coated with SiO2 was obtained by suction filtration and washing, which was recorded as Al@SiO2;
[0035] (3) dissolving 5 g of stearic acid in 10 g of isopropanol to obtain a stearic acid solution;
[0036] The Al@SiO2 prepared in step (2) is fully dispersed in 150 g of ethanol, stirred and mixed evenly, and then the stearic acid solution is slowly added thereto. The mixture is stirred in a water bath at 40°C for 1 h. After the reaction is completed, the mixture is filtered and washed to obtain a multilayer structure-coated flaky aluminum powder, i.e., the corrosion-resistant modified water-based aluminum silver paste, which is denoted as Al@SiO2@FA.
[0037] Example 2: Preparation of corrosion-resistant modified water-based aluminum paste
[0038] (1) The preparation method of the modified aluminum-silver paste is basically the same as that of the embodiment, except that ethanol is replaced by ethylene glycol;
[0039] (2) Weigh 1 g of ethylenediamine and dissolve it in 10 g of isopropanol to obtain an ethylenediamine solution for later use;
[0040] The modified aluminum-silver paste obtained in step (1) was added to 150 g of ethylene glycol and mixed evenly, and then 10 g of alkaline silica sol with a mass concentration of 15% and the above-mentioned ethylenediamine solution were slowly added thereto for 3 h. After the addition was completed, the mixture was stirred and reacted at a water bath temperature of 45° C. for 6 h. After the reaction was completed, the aluminum-silver paste coated with SiO2 was obtained by suction filtration and washing, which was recorded as Al@SiO2;
[0041] (3) dissolving 2 g of stearic acid and 3 g of oleic acid in 10 g of isopropanol to obtain a fatty acid solution;
[0042] The Al@SiO2 prepared in step (2) is fully dispersed in 150 g of ethylene glycol, and after stirring and mixing evenly, the stearic acid solution is slowly added thereto. The mixture is stirred in a water bath at 40°C for 1 h. After the reaction is completed, the mixture is filtered and washed to obtain a multilayer structure-coated flaky aluminum powder, i.e., the corrosion-resistant modified water-based aluminum silver paste, which is denoted as Al@SiO2@FA.
[0043] Example 3: Preparation of corrosion-resistant modified water-based aluminum paste
[0044] (1) 50 g of the original aluminum silver paste was fully dispersed in 150 g of ethylene glycol monobutyl ether, and after stirring and dispersing for more than 1 hour, 5 g of vinyl trimethoxysilane and 5 g of water were added thereto, and the mixture was stirred and reacted at a water bath temperature of 45° C. for 1 hour; after the reaction was completed, the modified aluminum silver paste was obtained by suction filtration and washing;
[0045] (2) The preparation of aluminum-silver paste coated with SiO2 was the same as in Example 2, except that ethylene glycol was replaced by ethylene glycol monobutyl ether;
[0046] (3) dissolving 2 g of stearic acid in 10 g of isopropanol to obtain a stearic acid solution;
[0047] The Al@SiO2 prepared in step (2) is fully dispersed in 150 g of ethylene glycol monobutyl ether, and after stirring and mixing evenly, the stearic acid solution is slowly added thereto. The mixture is stirred in a water bath at 40°C for 1 h. After the reaction is completed, the mixture is filtered and washed to obtain a multilayer structure capsule-coated flaky aluminum powder, i.e., the corrosion-resistant modified water-based aluminum silver paste, which is denoted as Al@SiO2@FA.
[0048] Example 4: Preparation of corrosion-resistant modified water-based aluminum paste
[0049] (1) The preparation of modified aluminum silver paste is the same as in Example 3, except that the silane coupling agent is changed to KH570, and the amount of silane coupling agent is 2.5 g;
[0050] (2) The preparation of aluminum-silver paste coated with SiO2 was the same as in Example 3, except that the amount of alkaline silica sol was changed to 10 g;
[0051] (3) dissolving 2 g of palmitic acid in 10 g of isopropanol to obtain a palmitic acid solution;
[0052] The Al@SiO2 prepared in step (2) is fully dispersed in 150 g of ethylene glycol monobutyl ether, and after stirring and mixing evenly, the palmitic acid solution is slowly added thereto, and the mixture is stirred in a water bath at 40°C for 1 hour. After the reaction is completed, the mixture is filtered and washed to obtain a multilayer structure capsule-coated flaky aluminum powder, i.e., the corrosion-resistant modified water-based aluminum silver paste, denoted as Al@SiO2@FA.
[0053] Example 5: Preparation of corrosion-resistant modified water-based aluminum paste
[0054] (1) The preparation of modified aluminum silver paste is the same as that of Example 4, except that the solvent 150 g of ethylene glycol monobutyl ether is changed to a mixed solvent of 75 g of ethylene glycol monobutyl ether and 75 g of isopropyl alcohol;
[0055] (2) The coating of SiO2 layer was the same as in Example 3, except that the reaction temperature was changed to 60°C;
[0056] (3) weighing 3 g of oleic acid and 2 g of linoleic acid and dissolving them in 10 g of ethylene glycol monobutyl ether to obtain a fatty acid solution;
[0057] The Al@SiO2 prepared in step (2) is fully dispersed in a mixed solvent of 150 g of ethylene glycol monobutyl ether and 75 g of isopropanol, and the fatty acid solution is slowly added thereto after stirring and mixing evenly. The mixture is stirred in a water bath at 70°C for 1 hour. After the reaction is completed, the mixture is filtered and washed to obtain a multilayer structure-coated flaky aluminum powder, i.e., the corrosion-resistant modified water-based aluminum silver paste, which is denoted as Al@SiO2@FA.
[0058] Example 6: Preparation of corrosion-resistant modified water-based aluminum paste
[0059] (1) The preparation of modified aluminum-silver paste is the same as in Example 5;
[0060] (2) Weigh 3 g of ethylenediamine and dissolve it in 10 g of isopropanol to obtain an ethylenediamine solution for later use;
[0061] The modified aluminum-silver paste obtained in step (1) is added to a mixed solvent of 75 g of ethylene glycol monobutyl ether and 75 g of isopropanol and mixed evenly, and then 10 g of alkaline silica sol with a mass concentration of 30% and the above-mentioned ethylenediamine solution are slowly added thereto for 3 hours. After the addition is completed, the mixture is stirred and reacted at a water bath temperature of 45° C. for 4 hours. After the reaction is completed, the aluminum-silver paste coated with SiO2 is obtained by suction filtration and washing, which is recorded as Al@SiO2;
[0062] (3) The preparation of the corrosion-resistant modified water-based aluminum-silver paste was the same as in Example 5, except that the reaction temperature was changed to 60° C.;
[0063] Example 7: Preparation of corrosion-resistant modified water-based aluminum paste
[0064] (1) The preparation of modified aluminum-silver paste was the same as in Example 5, except that the silane coupling agent was changed to KH550 and the stirring time was 3 h;
[0065] (2) Weigh 1 g of aqueous ammonia and dissolve it in 10 g of isopropanol to obtain an aqueous ammonia solution for later use;
[0066] The modified aluminum-silver paste obtained in step (1) is added to a mixed solvent of 75 g of ethylene glycol monobutyl ether and 75 g of isopropanol and mixed evenly, and then 10 g of alkaline silica sol with a mass concentration of 20% and the above-mentioned ammonia solution are slowly added thereto for 3 hours. After the addition is completed, the mixture is stirred and reacted at a water bath temperature of 45° C. for 4 hours. After the reaction is completed, the aluminum-silver paste coated with SiO2 is obtained by suction filtration and washing, which is recorded as Al@SiO2;
[0067] (3) weighing 2.5 g of stearic acid and 2.5 g of palmitic acid and dissolving them in 10 g of isopropanol to obtain a fatty acid solution;
[0068] The Al@SiO2 prepared above was fully dispersed in a mixed solvent of 75g ethylene glycol monobutyl ether and 75g isopropanol, and stirred to mix evenly to form a third dispersion. The fatty acid solution was slowly added dropwise to the aluminum silver paste dispersion, and stirred for reaction at a water bath temperature of 60°C for 1h. After the reaction was completed, the multilayer structure-coated flaky aluminum powder (Al@SiO2@FA) was obtained by suction filtration and washing;
[0069] Example 8: Preparation of corrosion-resistant modified water-based aluminum paste
[0070] (1) 50 g of the original aluminum silver paste was fully dispersed in 150 g of isopropanol, and after stirring and dispersing for more than 1 hour, 5 g of KH550 and 5 g of water were added thereto, and the mixture was stirred and reacted at a water bath temperature of 45° C. for 3 hours; after the reaction was completed, the modified aluminum silver paste was obtained by suction filtration and washing;
[0071] (2) Weigh 1 g of aqueous ammonia and dissolve it in 10 g of isopropanol to obtain an aqueous ammonia solution for later use;
[0072] The modified aluminum-silver paste obtained in step (1) is added to a mixed solvent of 150 g isopropanol and mixed evenly, and then 15 g of alkaline silica sol with a mass concentration of 30% and the above-mentioned ammonia solution are slowly added thereto for 3 hours. After the addition is completed, the mixture is stirred and reacted at a water bath temperature of 60° C. for 4 hours. After the reaction is completed, the aluminum-silver paste coated with SiO2 is obtained by suction filtration and washing, which is recorded as Al@SiO2;
[0073] (3) Weighing 2 g of palmitic acid and 1 g of oleic acid and dissolving them in 10 g of isopropanol to obtain a fatty acid solution;
[0074] The Al@SiO2 prepared above was fully dispersed in a mixed solvent of 150g isopropanol, and stirred to mix evenly to form a third dispersion. The fatty acid solution was slowly added dropwise to the aluminum silver paste dispersion, and stirred for reaction at a water bath temperature of 60°C for 1h. After the reaction was completed, the multilayer structure capsule-coated flaky aluminum powder was obtained by filtration and washing, i.e., the corrosion-resistant modified water-based aluminum silver paste, denoted as Al@SiO2@FA.
[0075] Example 9: Preparation of corrosion-resistant modified water-based aluminum paste
[0076] (1) The preparation of modified aluminum silver paste was the same as in Example 8, except that the amount of KH550 was changed to 2.5 g;
[0077] (2) Weigh 3 g of aqueous ammonia and dissolve it in 10 g of isopropanol to obtain an aqueous ammonia solution for later use;
[0078] The modified aluminum-silver paste obtained in step (1) is added to a mixed solvent of 150 g isopropanol and mixed evenly, and then 15 g of alkaline silica sol with a mass concentration of 30% and the above-mentioned ammonia solution are slowly added thereto for 3 hours. After the addition is completed, the mixture is stirred and reacted at a water bath temperature of 60° C. for 4 hours. After the reaction is completed, the aluminum-silver paste coated with SiO2 is obtained by suction filtration and washing, which is recorded as Al@SiO2;
[0079] (3) weighing 3 g of palmitic acid and dissolving it in 10 g of isopropanol to obtain a palmitic acid solution;
[0080] The Al@SiO2 prepared above is fully dispersed in a mixed solvent of 150g isopropanol, and stirred to mix evenly to form a third dispersion. The palmitic acid solution is slowly added dropwise to the aluminum silver paste dispersion, and stirred for reaction at a water bath temperature of 60°C for 1h. After the reaction is completed, the multilayer structure-coated flaky aluminum powder is obtained by suction filtration and washing, that is, the corrosion-resistant modified water-based aluminum silver paste, which is recorded as Al@SiO2@FA.
[0081] from Figure 1 It can be seen that 1110cm -1 The broad absorption peaks near 798 cm -1 The absorption peaks at 954 cm-1 are the antisymmetric stretching vibration and symmetric stretching vibration absorption peaks of Si-O-Si bond. -1 The absorption peak at 1700cm is the stretching vibration peak of Si-OH bond, and the surface SiO2 is successfully deposited on the surface of aluminum-silver paste. -1 There is a stretching vibration peak of the C=O bond at , indicating that the fatty acid hydrophobic organic layer is coated on the surface of the aluminum-silver paste.
[0082] from Figure 2 It can be seen that there are only a few mechanical scratches and metal debris on the surface of the original aluminum sheet caused by the production process. Figure 2 (b) and Figure 2 (c) shows that the surface of the aluminum sheet is completely covered by SiO2 nanoparticles and fatty acid organic layer.
[0083] This example also examines the coating content, corrosion resistance, water surface floating, whiteness, brightness and other properties of the industrial original aluminum silver paste (comparative example) and the floating multi-layer structure coated aluminum silver paste water-based coating obtained in Examples 1 to 9, and the specific method is as follows:
[0084] S1. Coating content
[0085] According to the test method of the Chemical Industry Standard HG / T 2456.3-2015 of the People's Republic of China, the coating layer content of the multilayer structure coated floating aluminum silver paste synthesized in the above Examples 1 to 9 was measured and expressed as mass percentage. The results are shown in Table 1.
[0086] S2. Corrosion resistance
[0087] The industrial original aluminum paste (comparative example) and the multilayer structure coated floating aluminum paste water-based coating synthesized in Examples 1 to 9 were fully dispersed in a NaOH solution with a pH of 11.4. The volume of H2 generated within 1 hour was collected to measure the corrosion resistance of the prepared coated flaky aluminum powder in an alkaline environment; the results are shown in Table 1.
[0088] S3. Floatability
[0089] According to the test method of the Chemical Industry Standard HG / T 2456.1-2013 of the People's Republic of China, the water hiding power of the industrial original aluminum paste (comparative example) and the multi-layer structure coated floating aluminum paste water-based coating synthesized in Examples 1 to 9 was measured. The results are shown in Table 1.
[0090] S4. Whiteness and brightness analysis
[0091] 1.00g of industrial original aluminum silver paste and the multilayer structure-coated floating aluminum silver paste water-based coating synthesized in Examples 1 to 9 were fully mixed with an acetone solution of polymethyl methacrylate (PMMA). The suspension was evenly coated on a glass plate and dried at room temperature to obtain a 0.2mm thick coating. The whiteness index (WI) and brightness index (BI) of the coating were measured using a Datacolor 600 spectrophotometer. The results are shown in Table 1.
[0092] Table 1. Performance study of industrial original aluminum paste and floating water-based aluminum paste
[0093]
[0094]
[0095] It can be seen from Table 1 that compared with the water-based aluminum-silver paste in the prior art, the water-based aluminum-silver paste prepared by the method of the present invention has a water surface hiding power increased from 0 to 52200-127200 cm compared with the untreated industrial original aluminum-silver paste. 2 / g, with good floating properties, improved corrosion resistance, and no significant reduction in whiteness and brightness. This shows that the prepared water-based aluminum silver paste has high surface tension, good corrosion resistance and gloss, and can be widely used in various water-based coating systems.
[0096] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing a corrosion-resistant modified water-based aluminum-silver paste, It is characterized in that The preparation method comprises: The original oily aluminum paste raw material is dispersed in an alcohol or ether solvent to form a dispersion, and the silane coupling agent is hydrolyzed on the surface of the aluminum powder to eliminate the organic modifiers on the surface of the oily aluminum paste, and the surface is modified to obtain aluminum flakes; alkaline silica sol is used as a raw material to prepare SiO 2 Coated aluminum flake powder, then on SiO 2 The surface of the coated flaky aluminum powder is coated with a fatty acid hydrophobic organic monomer to obtain a floating flaky aluminum powder coated with a multilayer structure, that is, the corrosion-resistant modified water-based aluminum-silver paste.
2. The method for preparing the corrosion-resistant modified water-based aluminum-silver paste according to claim 1, It is characterized in that The alcohol or ether solvent includes one or more of ethanol, isopropanol, ethylene glycol or ethylene glycol butyl ether; The silane coupling agent includes any one of KH550 (γ-aminopropyltriethoxysilane), KH570 (γ-methacryloxytrimethoxysilane), methyltrimethoxysilane or vinyltrimethoxysilane; The fatty acid hydrophobic organic monomer includes one or more of stearic acid, palmitic acid, oleic acid or linoleic acid.
3. The method for preparing the corrosion-resistant modified water-based aluminum-silver paste according to claim 1, It is characterized in that The preparation steps include: (1) dispersing the original aluminum paste raw material in an alcohol or ether solvent, adding a silane coupling agent and water thereto, and then stirring and reacting at a certain temperature, and filtering after the reaction is completed to obtain a modified aluminum paste; (2) Dispersing the modified aluminum silver paste in an alcohol or ether solvent, then slowly dropping the alkaline silicon solution and the alkaline solution therein, mixing and stirring the mixture for reaction, filtering and washing after the reaction is completed to obtain SiO 2 Coated aluminum flake powder; (3) SiO 2 The coated flaky aluminum powder is dispersed in an alcohol or ether solvent, and then an isopropanol solution of a fatty acid hydrophobic organic monomer is added dropwise thereto, and the mixture is vigorously stirred for reaction. After the reaction is completed, the mixture is filtered and washed to obtain the corrosion-resistant modified water-based aluminum silver paste.
4. The method for preparing the corrosion-resistant modified water-based aluminum-silver paste according to claim 3, It is characterized in that In step (1), the mass ratio of the original aluminum-silver paste raw material, the silane coupling agent, and water is 50 g: 2.5-5 g: 5 g; and the stirring reaction conditions are: reacting at 45-60° C. for 1-3 hours.
5. The method for preparing the corrosion-resistant modified water-based aluminum-silver paste according to claim 3, It is characterized in that In step (2), the mass ratio of the modified aluminum-silver paste, the alkaline silicon solution, and the alkaline solution is 50 g: 5-15 g: 1-3 g; The mass concentration of the alkaline silicon solution is 15-30%.
6. The method for preparing the corrosion-resistant modified water-based aluminum-silver paste according to claim 3, It is characterized in that The alkaline solution includes any one of aqueous ammonia, ethylenediamine or triethylamine.
7. The method for preparing the corrosion-resistant modified water-based aluminum-silver paste according to claim 3, It is characterized in that In step (2), the mixing and stirring reaction conditions are: stirring the mixing and reaction at 45-60° C. for 4-6 hours.
8. The method for preparing the corrosion-resistant modified water-based aluminum-silver paste according to claim 3, It is characterized in that In step (3), the SiO 2 The mass ratio of the coated aluminum flake powder and the fatty acid hydrophobic organic monomer is 50g:2-5g; The conditions for the vigorous stirring reaction are: vigorous stirring reaction at 40-70° C. for 1-3 hours.
9. The corrosion-resistant modified water-based aluminum silver paste prepared by the method according to any one of claims 1 to 8, It is characterized in that The surface of the modified water-based aluminum-silver paste is sequentially coated with an alkaline silica sol capsule film and a fatty acid organic film; the alkaline silica sol capsule film has a high degree of density and is firmly connected to the surface of the aluminum sheet; the carboxyl group of the fatty acid and the hydroxyl group of the alkaline silica sol capsule film are bonded to each other to form a fatty acid organic film with a dense surface.
10. The corrosion-resistant modified water-based aluminum silver paste according to claim 9 is widely used in automotive coatings, industrial coatings, plastic materials or printing inks.
Citation Information
Cited By
Water-based aluminum pigment as well as preparation method and application thereof
CN121045859A
